Problemática del impuesto a la renta que enfrentan los clubes de fútbol en el Perú - Anticona Villanueva, Diana Esmeralda (2019)
Through Law 29504, which promotes the transformation and participation of Professional Football Sports Clubs into Public Limited Companies, Article 5 introduces for the first time the open public limited company as the legal form of sports clubs. This article develops the Income Tax (IR) from the perspective of a sports club operating as a company. In this sense, the Income Tax Law does not provide for any special treatment or special regime for clubs; however, frequent problems faced by such entities have been identified, such as: expenses incurred by football clubs in hiring professional footballers; the tax category and determine the payment to be made in hiring technical directors, if it corresponds to the fourth or fifth category; as well as expenses incurred by the football club in favor of sports institutions.